Tundish slag line dry material
By using a composite binder of trisodium phosphate hexahydrate, sodium metasilicate, adipic acid, calcium carbonate and vermiculite in the magnesium dry material in the tundra, the environmental protection and strength of the phenolic resin binder are solved. The problem is that the fire resistance and thermal shock resistance of the dry material of the intermediate enclosure slag line has been significantly improved, and the material performance has been comprehensively optimized.
Patent Information
- Application Number
- CN202411260254.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-10
AI Technical Summary
The phenolic resin binder in traditional tundra magnesium dry material releases a large amount of volatile organic compounds during the heating and curing process, resulting in health risks and environmental protection problems. At the same time, its strength is insufficient, resulting in dry material peeling and tundra collapse accidents, limiting The operation efficiency and safety of continuous casting production lines are achieved.
Using trisodium phosphate hexahydrate, sodium metasilicate, adipic acid, calcium carbonate and vermiculite as new composite binding agents, the formation of stable complexes, silicate and phosphate glass phases and crosslinking networks Structure, expanded layered structure and microporous thermal insulation structure significantly improve the medium-temperature high-temperature strength, corrosion resistance and thermal shock resistance of dry materials.
It significantly reduces harmful gas emissions, improves the medium temperature, high temperature strength and thermal shock resistance of the dry materials in the middle slag line, extends the service life, reduces occupational health risks, meets green production requirements, and enhances the stability of the continuous casting process. Sex and safety.
Smart Images

Figure BDA0005035348100000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of tundish refractory materials, and in particular relates to a tundish slag line dry material. Background Art
[0002] In the modern steel production process, the tundish is a key component of the continuous casting process, and the performance of its refractory materials directly affects the purity of the molten steel, production efficiency and cost control. Magnesium dry material in the tundish, as a commonly used refractory material, plays a vital role in maintaining good molten steel flow characteristics, reducing inclusions and improving the quality of the ingot. However, in the selection of binders, phenolic resin is generally used as the main bonding component in the traditional magnesium dry material in the tundish. Although phenolic resin is widely used due to its good bonding properties and easy construction, several problems exposed in its practical application are increasingly attracting attention from the industry.
[0003] During the heating and curing process, phenolic resin releases a large amount of volatile organic compounds (VOCs). These chemicals not only have a strong pungent smell, posing a potential threat to human health, but also make employees prone to respiratory diseases and other occupational health problems in such a long-term working environment. In serious cases, it even violates increasingly stringent environmental regulations. Therefore, it is imperative to find a low-VOC or VOC-free environmentally friendly binder. In addition, the strength performance of magnesium dry materials combined with phenolic resin under medium and high temperature conditions is not satisfactory. During the medium-temperature baking process and during use, they are subjected to long-term erosion by molten steel, as well as thermal shock caused by frequent temperature changes. Due to the low strength of the dry materials, the dry materials will peel off, and even the tundish collapse accident will occur, which directly limits the service life of the tundish, reduces the operating efficiency of the continuous casting production line, and brings certain safety risks.
[0004] Although there are several environmentally friendly binders on the market, such as water glass and phosphate binders, their comprehensive performance, especially the balance of strength, corrosion resistance, and construction convenience, is still difficult to fully meet the high standards of modern continuous casting technology. Summary of the invention
[0005] In view of the environmental protection problems of the phenolic resin binder in the existing tundish magnesium dry material and the problem of severe erosion and peeling of the dry material due to insufficient strength of the tundish magnesium dry material during use, the present invention provides a tundish slag line dry material, which overcomes the defects of the traditional phenolic resin binder, can significantly improve the strength of the tundish dry material, and at the same time ensures the green and environmental protection of the production environment.
[0006] The scheme adopted by the present invention to solve the technical problem is: a tundish slag line dry material, wherein the mass percentage of each raw material component in the tundish slag line dry material is: 26-30% of 3-1mm fused magnesia, 22-28% of 1-0mm fused magnesia, 20-27% of 200-mesh fused magnesia, 1.5-2% of trisodium phosphate hexahydrate, 2-2.5% of sodium metasilicate nonahydrate, 1-1.5% of adipic acid, 4-5% of calcium carbonate, 0.3-0.5% of vermiculite, and the balance is 5-3mm fused magnesia.
[0007] Furthermore, the tundish slag line dry material comprises 28% 3-1mm fused magnesia, 25% 1-0mm fused magnesia, 24% 200-mesh fused magnesia, 1.8% trisodium phosphate hexahydrate, 2.2% sodium metasilicate nonahydrate, 1.2% adipic acid, 4.4% calcium carbonate, 0.4% vermiculite, and the remainder is 5-3mm fused magnesia.
[0008] Furthermore, the MgO content in the fused magnesia is ≥91%.
[0009] Furthermore, the trisodium phosphate hexahydrate, sodium metasilicate nonahydrate, and adipic acid are all of industrial grade.
[0010] Furthermore, the calcium carbonate particle size is 2000 mesh, CaCO 3 Content ≥98%.
[0011] Furthermore, the vermiculite has a particle size of 325 mesh, and the MgO content in the vermiculite is ≥21%, and the Al 2 O 3 Content ≥14%, Fe 2 O 3 Content ≤7%.
[0012] Furthermore, the sum of the mass percentages of trisodium phosphate hexahydrate, sodium metasilicate nonahydrate and adipic acid in the dry material of the tundish slag line is 4.8-5.8%.
[0013] Furthermore, when the dry material of the tundish slag line is packaged, the baking time is ≥1.5h, and the inner wall temperature of the working layer membrane is ≥280°C.
[0014] The present invention adopts trisodium phosphate hexahydrate. As an alkaline binder, trisodium phosphate hexahydrate can form a stable complex at a relatively low temperature when combined with water vapor, thereby providing good initial bonding force and facilitating the molding and solidification of dry materials. At high temperatures, phosphate can react with magnesium materials to form a glass phase, thereby enhancing the high-temperature structural strength and corrosion resistance of refractory materials. During the heating process, phosphate ions generated by the decomposition of trisodium phosphate react with magnesium ions to generate refractory magnesium phosphate salts. This reaction not only enhances the high-temperature stability of the dry materials, but also effectively fills the pores inside the dry materials, thereby improving the compactness.
[0015] The present invention adopts sodium metasilicate nonahydrate, which has high alkalinity and good water solubility, is helpful for uniform mixing of dry materials and evaporation of water during the curing process. When heated, the sodium metasilicate nonahydrate gradually loses crystal water and is converted into a silicon dioxide network. The network structure can not only increase the refractoriness of the material, but also form fine closed pores, improve the thermal insulation performance and thermal stress resistance of the material. At the same time, the silicon-oxygen network structure formed by the decomposition of sodium metasilicate nonahydrate at high temperature can significantly improve the high-temperature strength and thermal shock resistance of the material.
[0016] The present invention adopts adipic acid as an organic acid, which undergoes a polycondensation reaction with the alkaline components in the dry material during high-temperature heating to form a cross-linked network structure, which helps to disperse stress and prevent the generation of cracks, thereby improving the overall strength and crack resistance of the dry material.
[0017] The present invention adopts calcium carbonate. At high temperature, the calcium carbonate decomposes into calcium oxide and carbon dioxide. The calcium oxide further reacts with other components to help form a denser structure, which can adjust the density and porosity of the dry material, improve the volume stability of the dry material, and reduce the production cost. The released carbon dioxide can play the role of a foaming agent to a certain extent, which helps to form a microporous structure and enhance the insulation effect.
[0018] The present invention adopts vermiculite, and the layered structure of vermiculite will expand between the hydrated layers when heated, forming many tiny air gaps. These gaps serve as insulation layers, effectively slowing down heat transfer, making it have excellent expansion and heat insulation properties, and at the same time increasing the elasticity of the material, which can significantly improve the thermal shock resistance of the dry material and reduce material damage caused by rapid temperature changes.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The present invention adopts a new composite binder system, which greatly reduces the emission of harmful gases and the odor in the workplace compared with the traditional phenolic resin binder, significantly improves the working environment of employees, reduces occupational health risks, and meets the requirements of modern industry for green production and sustainable development;
[0021] 2. The trisodium phosphate hexahydrate and sodium metasilicate nonahydrate selected in the present invention can react with fused magnesia at high temperature to form stable and high-strength silicate and phosphate glass phases, effectively improving the medium-temperature and high-temperature strength of the dry material, increasing the service life of the dry material, and enhancing the medium-temperature and high-temperature strength of the dry material of the tundish slag line;
[0022] 3. The present invention introduces adipic acid and vermiculite to form a cross-linked network structure and an expanded layered structure, which significantly enhances the toughness and thermal shock resistance of the dry material in the tundish slag line, reduces the cracking and peeling of the material caused by sudden temperature changes, and improves the stability and safety of the continuous casting process;
[0023] 4. The present invention uses calcium carbonate. The carbon dioxide produced by the decomposition of calcium carbonate and the interlayer expansion of vermiculite work together to form a good microporous insulation structure, which effectively isolates the external high temperature, reduces the temperature fluctuation of molten steel, and improves the volume stability of the dry material.
[0024] In summary, the present invention not only solves the environmental protection problem of traditional phenolic resin binder by adopting a new composite binder system, but also significantly improves the medium-temperature and high-temperature strength, corrosion resistance, thermal shock resistance and insulation performance of magnesium dry materials through the synergistic effect among the various components, thereby achieving comprehensive optimization of material properties and bringing innovation to the field of continuous casting tundish refractory materials. DETAILED DESCRIPTION
[0025] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] The present invention provides a technical solution for dry material of tundish slag line:
[0027] A tundish slag line dry material, wherein the mass percentages of various raw material components in the tundish slag line dry material are: 26-30% of 3-1mm fused magnesia, 22-28% of 1-0mm fused magnesia, 20-27% of 200-mesh fused magnesia, 1.5-2% of trisodium phosphate hexahydrate, 2-2.5% of sodium metasilicate nonahydrate, 1-1.5% of adipic acid, 4-5% of calcium carbonate, 0.3-0.5% of vermiculite, and the remainder is 5-3mm fused magnesia.
[0028] As a preferred embodiment of the present invention, the tundish slag line dry material comprises 28% 3-1mm fused magnesia, 25% 1-0mm fused magnesia, 24% 200-mesh fused magnesia, 1.8% trisodium phosphate hexahydrate, 2.2% sodium metasilicate nonahydrate, 1.2% adipic acid, 4.4% calcium carbonate, 0.4% vermiculite, and the remainder is 5-3mm fused magnesia.
[0029] The present invention adopts 5-3mm fused magnesia. The fused magnesia particles with larger particle size mainly play a skeleton support role in the dry material of the tundish slag line, which can enhance the overall strength and anti-scouring ability of the material, help reduce the shrinkage of the material caused by temperature changes during sintering or use, maintain the stability of the material, and the appropriate particle gap can also improve the air permeability of the material, which is beneficial to the flow of molten steel in the tundish and the uniform temperature distribution; 3-1mm fused magnesia is used to form a stable skeleton system together with 5-3mm particles. Through reasonable particle size matching, the packing density and uniformity of the dry material can be improved, the porosity can be reduced, and the erosion resistance and anti-scouring property of the dry material can be improved; 1-0mm Fused magnesia with smaller particle size can fill the gaps between large particles, improve the compactness and density of dry materials, and further improve the thermal shock resistance and erosion resistance of dry materials by refining the particle size distribution. At the same time, small particles of 1-0mm have a larger specific surface area, which is conducive to the diffusion and reaction of materials during sintering and accelerates the sintering process. Using 200-mesh fused magnesia, ultra-fine fused magnesia particles can significantly refine the microstructure of the material and improve the uniformity and density of the dry materials. The refined structure helps to improve the strength, hardness and wear resistance of the dry materials, while enhancing the permeability and erosion resistance of the dry materials, and can further form a more dense and uniform sintered body.
[0030] As a preferred embodiment of the present invention, the MgO content in the fused magnesia is ≥ 91%.
[0031] The present invention adopts high-purity fused magnesia as raw material. The high-purity fused magnesia has large crystal grains and dense structure during the melting process. The tundish slag line dry material prepared by the fused magnesia also has good structural stability. The fused magnesia with high MgO content has strong resistance to slag erosion. The prepared tundish slag line dry material can also have good refractoriness and compressive strength, can maintain stable performance in a high temperature environment, and effectively prolongs the service life of the tundish.
[0032] As a preferred embodiment of the present invention, the trisodium phosphate hexahydrate, sodium metasilicate nonahydrate, and adipic acid are all of industrial grade.
[0033] The present invention uses industrial-grade trisodium phosphate hexahydrate, sodium metasilicate nonahydrate and adipic acid as raw materials, which have high purity and stable chemical composition. These characteristics help reduce the impurity content in the tundish slag line dry material, improve the overall performance and quality of the tundish slag line dry material, and are not prone to produce harmful material reactions during the preparation process, which is conducive to controlling the performance and stability of the tundish slag line dry material. These raw materials generate less waste and pollutants during use and are easy to handle and recycle. At the same time, industrial-grade raw materials also help reduce harm to the human body and the environment.
[0034] As a preferred embodiment of the present invention, the calcium carbonate particle size is 2000 mesh, CaCO 3 Content ≥98%.
[0035] The present invention selects high-purity calcium carbonate, which reduces the adverse effects of impurities on the performance of the dry material, helps to improve the overall quality and stability of the dry material, and the fine-grained calcium carbonate particles are conducive to forming a tighter and more uniform microstructure in the dry material. The fine particles can fill more gaps and improve the density and strength of the castable.
[0036] As a preferred embodiment of the present invention, the vermiculite has a particle size of 325 mesh, and the MgO content in the vermiculite is ≥ 21%, and the Al content in the vermiculite is ≥ 21%. 2 O 3 Content ≥14%, Fe 2 O 3 Content ≤7%.
[0037] The present invention uses 325 mesh vermiculite, which helps to achieve better mixing uniformity in the preparation process. The fine particles can also be more effectively filled in the pores of the dry material, thereby improving the density and strength of the material. The high MgO content can significantly improve the refractory performance of the dry material of the tundish slag line, extend the service life, and enhance the thermal stability of the material, thereby reducing cracking and peeling caused by temperature changes. The appropriate amount of Al 2 O 3 It helps to improve the overall mechanical properties of dry materials, improve the chemical stability of materials, and resist the erosion of molten steel and slag; a small amount of Fe 2 O 3 It can reduce the contamination of molten steel by iron generated during the use of materials, which is beneficial to maintain the cleanliness of molten steel. 2 O 3 Helps maintain the excellent properties of the material.
[0038] As a preferred embodiment of the present invention, the sum of the mass percentages of trisodium phosphate hexahydrate, sodium metasilicate nonahydrate and adipic acid in the dry material of the tundish slag line is 4.8-5.8%.
[0039] The synergistic effect of trisodium phosphate hexahydrate, sodium metasilicate nonahydrate and adipic acid in the dry material can significantly improve the refractoriness, corrosion resistance, uniformity and density of the material, thereby improving the service life and performance stability of the dry material. The present invention can achieve effective cost control while ensuring performance through a reasonable ratio of the three raw materials, while ensuring that high-quality tundish slag line dry material can be stably obtained in the actual production process.
[0040] As a preferred embodiment of the present invention, when making dry materials on the tundish slag line, the baking time is ≥1.5h, and the inner wall temperature of the working layer membrane is ≥280°C.
[0041] The extension of the baking time and the increase in the temperature of the inner wall of the working layer membrane are conducive to the full reaction and sintering of the binder in the dry material to form a denser and stronger structure, which can not only improve the mechanical strength of the dry material, but also enhance its corrosion resistance, thereby extending the service life of the tundish. Long-term baking at high temperature can fully remove the moisture and volatiles in the dry material, reduce the internal stress caused by temperature changes, help prevent the dry material from cracking and peeling during use, and improve the stability and reliability of the dry material.
[0042] Specific implementation cases:
[0043] A specific implementation of a tundish slag line dry material according to the present invention is provided below.
[0044] Embodiment 1:
[0045] The present embodiment provides a tundish slag line dry material, wherein the tundish slag line dry material has the following components in percentage by mass: 28% of 3-1 mm fused magnesia, 25% of 1-0 mm fused magnesia, 24% of 200 mesh fused magnesia, 1.8% of trisodium phosphate hexahydrate, 2.2% of sodium metasilicate nonahydrate, 1.2% of adipic acid, 4.4% of calcium carbonate, 0.4% of vermiculite, and the remainder is 5-3 mm fused magnesia.
[0046] Embodiment 2:
[0047] The present embodiment provides a tundish slag line dry material, wherein the tundish slag line dry material has the following components in percentage by mass: 30% of 3-1 mm fused magnesia, 22% of 1-0 mm fused magnesia, 25% of 200 mesh fused magnesia, 1.6% of trisodium phosphate hexahydrate, 2.3% of sodium metasilicate nonahydrate, 1.5% of adipic acid, 4.6% of calcium carbonate, 0.5% of vermiculite, and the remainder is 5-3 mm fused magnesia.
[0048] Embodiment 3:
[0049] The present embodiment provides a tundish slag line dry material, wherein the tundish slag line dry material has the following components in percentage by mass: 26% of 3-1 mm fused magnesia, 26% of 1-0 mm fused magnesia, 20% of 200 mesh fused magnesia, 1.9% of trisodium phosphate hexahydrate, 2.5% of sodium metasilicate nonahydrate, 1.4% of adipic acid, 4.2% of calcium carbonate, 0.3% of vermiculite, and the remainder is 5-3 mm fused magnesia.
[0050] Embodiment 4:
[0051] The present embodiment provides a tundish slag line dry material, wherein the tundish slag line dry material has the following components in percentage by mass: 27% of 3-1 mm fused magnesia, 28% of 1-0 mm fused magnesia, 22% of 200 mesh fused magnesia, 1.7% of trisodium phosphate hexahydrate, 2% of sodium metasilicate nonahydrate, 1.1% of adipic acid, 5% of calcium carbonate, 0.4% of vermiculite, and the remainder is 5-3 mm fused magnesia.
[0052] Embodiment 5:
[0053] The present embodiment provides a tundish slag line dry material, wherein the tundish slag line dry material has the following components in percentage by mass: 26% of 3-1 mm fused magnesia, 24% of 1-0 mm fused magnesia, 27% of 200 mesh fused magnesia, 1.5% of trisodium phosphate hexahydrate, 2.4% of sodium metasilicate nonahydrate, 1.3% of adipic acid, 4.8% of calcium carbonate, 0.5% of vermiculite, and the remainder is 5-3 mm fused magnesia.
[0054] Embodiment 6:
[0055] The present embodiment provides a tundish slag line dry material, wherein the tundish slag line dry material has the following components in percentage by mass: 28% of 3-1 mm fused magnesia, 25% of 1-0 mm fused magnesia, 23% of 200 mesh fused magnesia, 2% of trisodium phosphate hexahydrate, 2.1% of sodium metasilicate nonahydrate, 1% of adipic acid, 4% of calcium carbonate, 0.4% of vermiculite, and the remainder is 5-3 mm fused magnesia.
[0056] Comparative Example 1:
[0057] The comparative example provides a tundish slag line dry material. The tundish slag line dry material has the following components in percentage by mass: 30% 3-1mm fused magnesia, 22% 1-0mm fused magnesia, 25% 200-mesh fused magnesia, 0.5% trisodium phosphate hexahydrate, 2.3% sodium metasilicate nonahydrate, 1.5% adipic acid, 4.6% calcium carbonate, 0.5% vermiculite, and the remainder is 5-3mm fused magnesia. The content of trisodium phosphate hexahydrate in the comparative example is only 0.5%, which is relatively low.
[0058] Comparative Example 2:
[0059] The present comparative example provides a dry material for the tundish slag line. The dry material for the tundish slag line comprises the following components in percentage by mass: 26% 3-1mm fused magnesia, 26% 1-0mm fused magnesia, 20% 200-mesh fused magnesia, 1.9% trisodium phosphate hexahydrate, 2.5% sodium metasilicate nonahydrate, 0.4% adipic acid, 4.2% calcium carbonate, 0.3% vermiculite, and the remainder is 5-3mm fused magnesia. The content of adipic acid in the present comparative example is relatively low, only 0.4%.
[0060] Comparative Example 3:
[0061] The comparative example provides a dry material for the tundish slag line. The dry material for the tundish slag line has the following components in percentage by mass: 27% of 3-1mm fused magnesia, 28% of 1-0mm fused magnesia, 22% of 200-mesh fused magnesia, 1.7% of trisodium phosphate hexahydrate, 1% of sodium metasilicate nonahydrate, 1.1% of adipic acid, 5% of calcium carbonate, 0.4% of vermiculite, and the remainder is 5-3mm fused magnesia. The content of sodium metasilicate nonahydrate in the comparative example is as low as 1%.
[0062] Comparative Example 4:
[0063] The present comparative example provides a tundish slag line dry material, wherein the tundish slag line dry material comprises the following components in percentage by mass: 26% 3-1 mm fused magnesia, 24% 1-0 mm fused magnesia, 27% 200 mesh fused magnesia, 1.5% trisodium phosphate hexahydrate, 2.4% sodium metasilicate nonahydrate, 1.3% adipic acid, 4.8% calcium carbonate, and the remainder 5-3 mm fused magnesia. The present comparative example does not contain vermiculite.
[0064] Comparative Example 5:
[0065] The present comparative example provides a tundish slag line dry material, wherein the tundish slag line dry material comprises the following components in percentage by mass: 28% 3-1mm fused magnesia, 25% 1-0mm fused magnesia, 23% 200-mesh fused magnesia, 2% trisodium phosphate hexahydrate, 2.1% sodium metasilicate nonahydrate, 1% adipic acid, 2.5% calcium carbonate, 0.4% vermiculite, and the remainder is 5-3mm fused magnesia. The calcium carbonate content in the present comparative example is relatively low, only 2.5%.
[0066] The present invention prepares the sample of the dry material of the tundish slag line of Examples 1 to 6 and Comparative Examples 1 to 5 according to GB / T4513.5-2017 "Monomorphous Refractory Materials Part 5: Sample Preparation and Pretreatment", and the tests of bulk density, linear change rate, flexural strength and compressive strength are carried out according to GB / T 4513.6-2017 "Monolithic Refractory Part 6: Determination of Physical Properties" test method, qualified product test index range: the sum of the mass percentage of trisodium phosphate hexahydrate, sodium metasilicate nonahydrate and adipic acid is 4.8-5.8%; linear change rate (1100℃ / 3h) is 0-0.3%, linear change rate (1550℃ / 3h) is -1.5-0%; flexural strength (220℃ / 2h) is ≥1.6MPa, flexural strength (1100℃ / 3h) is ≥1.1MPa, flexural strength (1550℃ / 3h) is ≥3MPa; compressive strength (220℃ / 2h) is ≥6MPa, compressive strength (1100℃ / 3h) is ≥2.2MPa, compressive strength (1550℃ / 3h) is ≥9MPa. Test results are shown in Table 1:
[0067] Table 1 Test results of Examples 1 to 6 and Comparative Examples 1 to 5
[0068]
[0069] Comparative Example 1 is based on Example 2, reducing the addition amount of trisodium phosphate hexahydrate (below the limited range of the present invention), and correspondingly increasing the fused magnesia by 5-3 mm. As can be seen from Table 1, compared with Example 2, the flexural strength and compressive strength of Comparative Example 1 are significantly reduced, and the test results are unqualified. The test effect of Comparative Example 1 is significantly lower than that of Example 2.
[0070] Comparative Example 2 is based on Example 3, reducing the amount of adipic acid added (below the specified range of the present invention), and correspondingly increasing the fused magnesia by 5-3 mm. As can be seen from Table 1, compared with Example 3, the flexural strength and compressive strength of Comparative Example 2 are significantly reduced. Although the test results are qualified, the test effect of Comparative Example 2 is significantly lower than that of Example 3.
[0071] Comparative Example 3 is based on Example 4, reducing the addition amount of sodium metasilicate nonahydrate (below the limited range of the present invention), and correspondingly increasing the fused magnesia 5-3mm. It can be seen from Table 1 that compared with Example 4, the flexural strength and compressive strength of Comparative Example 3 are significantly reduced, and the test results are unqualified. The test effect of Comparative Example 3 is significantly lower than the test effect of Example 4.
[0072] Comparative Example 4 is based on Example 5, but the introduction of vermiculite is cancelled and fused magnesia is increased by 5-3 mm. As can be seen from Table 1, compared with Example 5, the flexural strength and compressive strength of Comparative Example 4 are significantly reduced. Although the test results are qualified, the test effect of Comparative Example 4 is significantly lower than that of Example 5.
[0073] Comparative Example 5 is based on Example 6, reducing the amount of calcium carbonate added (below the limited range of the present invention), and correspondingly increasing the fused magnesia by 5-3 mm. As can be seen from Table 1, compared with Example 6, the flexural strength and compressive strength of Comparative Example 5 are significantly reduced. Although the test results are qualified, the test effect of Comparative Example 5 is significantly lower than that of Example 6.
[0074] In summary, the present invention can effectively improve the flexural strength and compressive strength of the tundish slag line dry material by adding trisodium phosphate hexahydrate, sodium metasilicate nonahydrate, adipic acid, vermiculite and calcium carbonate. Through their synergistic effect in the dry material, the refractoriness, corrosion resistance, uniformity and density of the dry material can be significantly improved, thereby improving the service life and performance stability of the dry material. The present invention can achieve effective cost control while ensuring performance by reasonably proportioning the three raw materials of trisodium phosphate hexahydrate, sodium metasilicate nonahydrate and adipic acid, while ensuring that high-quality tundish slag line dry material can be stably obtained in the actual production process.
[0075] The above description is only a preferred embodiment of the present invention and does not limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A dry material for tundish slag line, Features: The mass percentage of each raw material component in the tundish slag line dry material is: 26-30% of 3-1mm fused magnesia, 22-28% of 1-0mm fused magnesia, 20-27% of 200-mesh fused magnesia, 1.5-2% of trisodium phosphate hexahydrate, 2-2.5% of sodium metasilicate nonahydrate, 1-1.5% of adipic acid, 4-5% of calcium carbonate, 0.3-0.5% of vermiculite, and the balance is 5-3mm fused magnesia.
2. The tundish slag line dry material according to claim 1, Features: The tundish slag line dry material comprises 28% of 3-1mm fused magnesia, 25% of 1-0mm fused magnesia, 24% of 200-mesh fused magnesia, 1.8% of trisodium phosphate hexahydrate, 2.2% of sodium metasilicate nonahydrate, 1.2% of adipic acid, 4.4% of calcium carbonate, 0.4% of vermiculite, and the remainder is 5-3mm fused magnesia.
3. The tundish slag line dry material according to claim 1, Features: The MgO content in the fused magnesia is ≥91%.
4. The tundish slag line dry material according to claim 1, Features: The trisodium phosphate hexahydrate, sodium metasilicate nonahydrate and adipic acid are all of industrial grade.
5. The tundish slag line dry material according to claim 1, Features: The calcium carbonate particle size is 2000 mesh, CaCO 3 Content ≥98%.
6. The tundish slag line dry material according to claim 1, Features: The vermiculite has a particle size of 325 meshes, and the content of MgO in the vermiculite is ≥21%. 2 O 3 Content ≥14%, Fe 2 O 3 Content ≤7%.
7. The tundish slag line dry material according to claim 1, Features: The sum of the mass percentages of trisodium phosphate hexahydrate, sodium metasilicate nonahydrate and adipic acid in the dry material of the tundish slag line is 4.8-5.8%.
8. The tundish slag line dry material according to claim 1, Features: When the tundish slag line is used for dry material packaging, the baking time is ≥1.5h, and the inner wall temperature of the working layer membrane is ≥280°C.
Citation Information
Patent Citations
Magnesia-calcia tundish dry vibrating material and preparation method thereof
CN106631056A
Carbon-free dry material for continuous casting tundish
CN113387686A
Plasma melting furnace refractory castable and preparation method thereof
CN114956797A
Laminar silicate intercalation compound with increased expanding volume, its preparing method and use
CN1508194A
Inflating basic irregular shape fireproof material
KR1019980046783A
